Transforming Play into Financial Learning: Non-Formal Educational Insights from GTA V Online - Wildan Ifkarun Nadhif Adz-Dzakky; Eko Suroso (Chatra: Jurnal Pendidikan dan Pengajaran, 2025)
Digital games are increasingly recognized as potential tools for non-formal learning, including enhancing financial literacy and social skills. This study was conducted to explore how Grand Theft Auto V Online, as a popular commercial game, can serve as a medium for non-formal education that facilitates understanding of digital economy concepts and financial literacy. Employing a qualitative approach with a descriptive design, the research involved participant observation where the researcher actively engaged as a player, supplemented by field notes and visual documentation as data collection techniques, analyzed through thematic analysis. The findings revealed that GTA V Online players engage in financial decision-making, management of virtual businesses, application of passive income strategies, and development of social skills through collaborative interactions. These results indicate that GTA V Online holds significant potential as a non-formal learning medium integrating entertainment with educational processes, although challenges remain regarding sensitive content and the necessity for appropriate pedagogical frameworks. This study contributes to expanding the understanding of commercial games as alternative educational tools while opening avenues for future research to quantitatively assess impacts and design more inclusive and safe pedagogical approaches.